PENYELESAIAN SENGKETA EKONOMI SYARIAH WANPRESTARSI SECARA NON LITIGASI BAIK YANG DIATUR HUKUM POSITIF, HUKUM ISLAM DAN HUKUM ADAT: RESOLUTION OF NON-LITIGATION SHARIA ECONOMIC DISPUTES WHICH IS REGULATED POSITIVE LAW, ISLAMIC LAW AND CUSTOM LAW - Siraji, Muhammad; Alamudi, Ichwan Ahnaz (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This research is motivated by the birth of Law No. 3 of 2006 on the amendment of Law No. 7 of 1989 on religious courts that have added authority to the religious courts in the field of sharia economics. Researchers want to know what are the ways to resolve economic disputes Sharia default in non-litigation both regulated punishable poitif, Islamic law and customary law. This research is a type of literature study or in the world of law is called juridical-normative legal research. This study shows that alternative dispute resolution with non-litigation model has several types and parts, including positive law such as Alternative Dispute Resolution, arbitration, and settlement of Sharia economic disputes through consumer institutions. Among them is the religion of peace and Justice.